Beyond Donor-Acceptor (D-A) Approach: Structure-Optoelectronic Properties-Organic Photovoltaic Performance Correlation in New D-A1-D-A2 Low-Bandgap Conjugated Polymers - Chochos, Christos L.; Drakopoulou, Sofia; Katsouras, Athanasios; Squeo, Benedetta M.; Sprau, Christian; Colsmann, Alexander; Gregoriou, Vasilis G.; Cando, Alex Palma; Allard, Sybille; Scherf, Ullrich; Gasparini, Nicola; Kazerouni, Negar; et al. (Macromolecular Rapid Communications, 2017)
Low-bandgap near-infrared polymers are usually synthesized using the common donor-acceptor (D-A) approach. However, recently polymer chemists are introducing more complex chemical concepts for better fine tuning of their optoelectronic properties. Usually these studies are limited to one or two polymer examples in each case study so far, though. In this study, the dependence of optoelectronic and macroscopic (device performance) properties in a series of six new D-A-D-A low bandgap semiconducting polymers is reported for the first time. Correlation between the chemical structure of single-component polymer films and their optoelectronic properties has been achieved in terms of absorption maxima, optical bandgap, ionization potential, and electron affinity. Preliminary organic photovoltaic results based on blends of the D-A-D-A polymers as the electron donor mixed with the fullerene derivative [6,6]-phenyl-C-butyric acid methyl ester demonstrate power conversion efficiencies close to 4% with short-circuit current densities (J ) of around 11 mA cm, high fill factors up to 0.70, and high open-circuit voltages (V s) of 0.70 V. All the devices are fabricated in an inverted architecture with the photoactive layer processed in air with doctor blade technique, showing the compatibility with roll-to-roll large-scale manufacturing processes.
Keywords: Conjugated polymers; Donor-acceptor; Low bandgap; Near-infrared; Organic photovoltaics

Crystallization of sensitizers controls morphology and performance in Si-/C-PCPDTBT-sensitized P3HT: ICBA ternary blends - Du, Xiaoyan; Jiao, Xuechen; Rechberger, Stefanie; Perea Ospina, Jose Dario; Meyer, Markus; Kazerouni, Negar; Spiecker, Erdmann; Ade, Harald; Brabec, Christoph; Fink, Rainer; Ameri, Tayebeh (Macromolecules, 2017)
Organic solar cells based on multinary components are promising to further boost the device performance. The complex interplay of the morphology and functionality needs further investigations. Here, we report on a systematic study on the morphology evolution of prototype ternary systems upon adding sensitizers featuring similar chemical structures but dramatically different crystallinity, namely poly(3-hexylthiophene) (P3HT) and indene-C-bis-adduct (ICBA) blends with poly[(4,4′-bis(2-ethylhexyl)dithieno[3,2-b:2′,3′-d]silole)-2,6-diyl-alt-(4,7-bis(2-thienyl)-2,1,3-benzothiadi-azole)-5,5′-diyl] (Si-PCPDTBT) and poly[2,6-(4,4-bis(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]-dithiophene)-alt-4,7-(2,1,3-benzothiadiazole)] (C-PCPDTBT), employing energy-filtered transmission electron microscopy (EFTEM) and resonant soft X-ray scattering (RSoXS). In addition, a combined density functional theory (DFT) and artificial neuronal network (ANN) computational approach has been utilized to calculate the solubility parameters and Flory-Huggins intermolecular parameters to evaluate the influence of miscibility on the final morphology. Our experiments reveal that the domain spacing and purity of ICBA-rich domains are retained in Si-PCPDTBT-based systems but are strongly reduced in C-PCPDTBT-based ternary systems. The P3HT fiber structure are retained at low sensitizer content but dramatically reduced at high sensitizer content. The theoretical calculations reveal very similar miscibility/compatibility between the two sensitizers and ICBA as well as P3HT. Thus, we conclude that mainly the crystallization of Si-PCPDTBT drives the nanostructure evolution in the ternary systems, while this driving force is absent in C-PCPDTBT-based ternary blends.
Keywords: Computation theoryDeep neural networksHigh resolution transmission electron microscopyMorphologyNeuronsOrganic solar cellsSiliconSolar cellsSolubilityTernary systemsTransmission electron microscopyX ray scattering

Improved charge carrier dynamics in polymer/perovskite nanocrystal based hybrid ternary solar cells - Soltani, Rezvan; Puscher, Bianka; Katbab, Ali Asghar; Levchuk, Ievgen; Kazerouni, Negar; Gasparini, Nicola; Camaioni, Nadia; Osvet, Andres; Batentschuk, Miroslaw; Fink, Rainer; Guldi, Dirk Michael; Ameri, Tayebeh (Physical Chemistry Chemical Physics, 2018)
Here, brand new ternary hybrid solar cells comprising perovskite nanocrystals (NCs) with a complementary absorption profile of the organic host matrix are reported. In particular, NH2CHNH2PbI3 (FAPbI3) perovskite NCs are implemented in bulk heterojunction organic solar cells based on the pDPP5T-2 electron donating polymer and a [6,6]-phenyl-C61-butyric acid methyl ester (PC61BM) acceptor at various loading amounts and the fabricated hybrid photovoltaics are thoroughly studied by employing different optoelectrical characterization methods. Current-voltage measurements and photoinduced charge carrier extraction by linear increasing voltage (photo-CELIV) reveal improved charge generation and charge transport properties upon incorporation of perovskite NCs into the photo-active layer of the hybrid solar cell. The power conversion efficiency (PCE) of the hybrid solar cell comprising 5% perovskite NCs is 10% enhanced compared to the organic reference, mainly due to the enlarged light harvesting and increased short circuit current density (Jsc). However, results suggest that introducing a higher amount of perovskite content induces bimolecular and trap-assisted recombination in the ternary devices. We perform a comprehensive transient absorption study of the charge transfer/transport mechanisms by employing femto-second pump-probe transient absorption spectroscopy (fs-TAS). fs-TAS measurements demonstrate a slower charge carrier recombination rate due to the introduction of perovskite NCs into the photoactive layer. Results reveal that DPP injects electrons from the singlet excited state into the perovskite NCs, which causes the desired cascading charge carrier transfer. In ternary blends, a small amount of FAPbI3 NCs provides an additional pathway in favor of the charge-separated state via the NCs, which, despite accelerating the depopulation of DPP's singlet excited state slightly slows down the charge-separation process between DPP and PC61BM. Interestingly, the loss processes are slowed down; an effect that is more important and, hence, explains the improved solar cell efficiency. © 2018 the Owner Societie